Effect of ZnO Addition on The Characteristics of Cotton Fabric in The Batik Fabric Dyeing Process - Fatimah, Siti; Kencana, Syaifunnisa Puspa; 'Aarifah, Shofwatul; Eskani, Istihanah Nurul (Eksergi, 2023)
For centuries, batik fabric has been a part of Indonesian culture and is recognized by UNESCO as an Intangible Cultural Heritage of Humanity. Batik fabric is essential for daily use and has become a part of Indonesian people, e.g., birth to death ceremonies. Besides some advantages of batik fabric made from cotton, it also has disadvantages because it quickly grows bacterial. Hence, it is essential to develop antibacterial properties on batik fabrics. This study used ZnO as an antibacterial agent. The mechanical properties and the colorfastness of fabrics have been evaluated to study the effect of ZnO application. The results showed that applying ZnO affected the mechanical properties of batik fabric by increasing the tensile strength and elongation at break. The result also showed that the ZnO did not affect the colorfastness of rubber and light by the similar value of untreated batik fabric.